Galectin-3 and Hector Battifora Mesothelial-1 immunohistochemical expression in 50 cases of thyroid neoplasms: a retrospective study done at tertiary care centre - Bhandari, Hitesha; Sharma, Anjali; Nilapwar, Rishikesh D.; Vyas, Praveena G.; Pawar, Aditya S. (International Surgery Journal, 2024)
Background: Diagnosis of thyroid carcinoma is not always straight forward on haematoxylin and eosin staining since nuclear features are inconsistent, overlapping and controversial. In regards to this, many studies on the role of immunohistochemical markers for diagnosis of malignant thyroid carcinoma are needed. In order to improve diagnostic accuracy, markers immunohistochemistry techniques have mainly emphasized on galectin-3 (Gal-3) and Hector Battifora Mesothelial-1 (HBME-1). However, results remain unsatisfactory. The aim of the present article was to establish the diagnostic accuracy of Gal-3 and HBME-1 markers, individual and in combination, in the differentiation of malignant and benign thyroid lesions. Methods: A total of 50 thyroidectomy specimens were studied over a period of 1.5 years from September 2019 to February 2021 at Bhagwan Mahaveer Cancer Hospital Research Centre, Jaipur which included 2 benign and 48 malignant thyroid neoplasms. Histopathologic evaluation of H&E stained sections was done and immunohistochemistry (IHC) staining for Gal-3 and HBME-1 was performed for all neoplasms. Results: For the immunohistochemistry technique, Gal-3 and HBME-1expression was significantly higher in malignant thyroid neoplasms in comparison to the benign neoplasms. Gal-3 expression for malignant neoplasms showed sensitivity of 97.92%, specificity of 50%. HBME-1 expression for malignant neoplasms showed sensitivity and specificity of 100% each. Gal-3 and HBME-1 are useful markers in differentiating benign and malignant thyroid neoplasms. Conclusions: This study demonstrated that both immunomarkers studied are sensitive and specific for diagnosis of benign and malignant thyroid lesions. However, the need of further studies for other molecular markers must continue in order to increase the diagnostic accuracy since a proportion of cases still show false-negative and false-positive tests.